Design Theory in the Research of Complex Cyber-Physical Systems with Organizational Artistic-Aesthetic and Culturological Structures in the Development of Post-Nonclassical Methodology Based on Nbic-Convergences - L. Zhukov, V; T. Zhukova, L (International Journal of Engineering and Technology, 2018)
In the theory of design, the processes (methodology) are explored of constructing complex cyber-physical systems with organizational artistic and aesthetic structures that arise in the course of civilizational crises in the context of a universal history in the evolution of its culture based on NBIC-convergences.Â Â